Hubungan Pengetahuan dengan Sikap Ibu Bayi Usia 6-12 Bulan dalam Pemberian MP-ASI - Puspitasari, Betristasia; Darmayanti, Rofik; Krisnawati, Dyah Ika; Sucipto (Jurnal Kesehatan, 2023)
Complementary foods for breast milk (MP-ASI) are foods or drinks that contain nutrients given to infants or children aged 6-24 months to meet nutritional needs other than breast milk. The state of malnutrition in infants and children is caused by improper breastfeeding habits and maternal ignorance about the benefits and correct ways of giving MP-ASI so that it affects the mother's attitude in giving MP-ASI. The study aims at  determine the relationship between knowledge and the attitude of mothers of mother of 6-12 months infants in Sidomulyo Village, Semen District, Kediri Regency. The research used a correlational design with a cross sectional approach. The sample of this study were 30 mothers of infants aged 6-12 months. Purposive sampling technique was used in this study. This study used knowledge and attitude questionnaires. The data obtained was then analyzed using chi square test. The results of the research showed that most respondents were well informed (14 respondents; 46.7%), and most respondents had a positive attitude towards the complementary feeding (21 respondents; 70%). The results of the chi square test obtained the p-value=0.000 (< 0.05), it means there is a relationship between knowledge and the attitude of mothers of 6-12 months infants in giving MP-ASI. Based on the results of the study, information about complementary foods for breast milk should be further improved by counseling, either from cadres or health workers, so that mothers will increase in their knowledge and have a positive attitude in giving complementary foods for breast milk.